(untitled) (Journal of Academic Research, 2021)
Surfaces quality is one of the most specified customer requirements for machine parts. The major indication of surfaces quality on machined parts is surface roughness. This research aims to study the cutting parameters (spindle speed, feed rate and depth of cut) and their effect on the surface roughness of low carbon steel workpieces machined under dry and wet turning conditions, using carbide cutting tool with a constant tool nose radius. Results revealed that, surface roughness is highly affected by the cutting parameters and also the cooling conditions